Guidance for Adolescents in Kota Atas Sabang Neighborhood Regarding the Dangers of Drug Abuse - Khalis, Mukhtar (International Journal Education and Computer Studies (IJECS), 2023)
Substances classified as narcotics play a crucial role in the realm of medicine and scientific advancement. However, the misuse of narcotics poses significant dangers, adversely affecting individuals and, ultimately, societies, nations, and states. Adolescents are increasingly susceptible to such misuse due to their developmental phase, characterized by experimentation that may lead to addiction. Their vulnerability is exacerbated by a lack of awareness regarding the perils of narcotics. This thesis aims to assess the extent of guidance provided by parents, religious figures, and the Sabang Police in addressing and guiding adolescents on the dangers of narcotics in the Kota Atas Sabang neighborhood. Additionally, it seeks to identify the factors contributing to adolescent narcotic abuse and to explore the efforts undertaken by law enforcement, educators, religious leaders, and community figures in preventing and addressing narcotics misuse among adolescents. The research methodology is descriptive, employing a combination of literature review and field research through observation, interviews, and questionnaires. The study includes 80 students from Sabang Public High School, three teachers, religious figures, and parents. The findings suggest that the guidance provided to adolescents regarding the dangers of narcotics is inadequate, influenced by a lack of guidance activities and attention from parents, religious figures, the Sabang Police, and educators. Consequently, it is recommended that community members actively involved in guidance activities intensify their efforts to enhance the effectiveness of these programs